PENGGUNAAN EKSTRAK BUNGA KENANGA TERHADAP KARAKTERISTIK FISIK SABUN SUSU - Adam, Firstan; Monica, Metha Monica; Fatati, Fatati (PT. Hasba Edukasi Mandiri, 2025)
Ylang-ylang (Cananga odorata) extract contains active compounds such as linalool, geraniol, and β-caryophyllene, which exhibit antimicrobial and antioxidant properties, making it a potential additive for skincare formulations. This study aimed to evaluate the physical characteristics of milk soap with the addition of ylang-ylang extract based on pH, moisture content, and foam stability. The research was conducted for 45 days, from June 6 to July 21, 2024, at the Laboratory of the Faculty of Animal Science, Jambi University. The materials used included fresh cow’s milk, coconut oil, palm oil, NaOH, and ylang-ylang extract. Treatments consisted of P0 = 0%, P1 = 5%, P2 = 10%, P3 = 15%, and P4 = 20% ylang-ylang extract, arranged in a Completely Randomized Design (CRD) with four replications. Observed parameters included pH, moisture content, and foam stability. Results showed that pH values ranged from 9.31 to 11.20, moisture content from 2.40% to 5.83%, and foam stability from 40.65% to 44.27%. Statistical analysis revealed that ylang-ylang extract had no significant effect (P>0.05) on all parameters. Thus, up to 20% extract addition did not significantly alter soap quality, and all physical properties remained within the acceptable standard range for solid soap.